Characterization of a novel thiosulfate-forming enzyme isolated from Desulfovibrio vulgaris. - Drake, H L (1977)
An enzyme that formed thiosulfate from bisulfite and trithionate was purified from extracts of Desulfovibrio vulgaris. This enzyme, designated as "thiosulfate-forming" enzyme, required the presence of both bisulfite and trithionate. Various 35S-labeling studies showed that thiosulfate was formed from bisulfite and the inner sulfur atom of trithionate. This involved a nucleophilic attack by the bisulfite ion, resulting in the displacement of the two outer sulfonate groups of trithionate that recycled to participate as free bisulfite in subsequent reactions. This reaction required a reduction, presumably by a concerted mechanism with thiosulfate formation. The natural electron carrier cytochrome c3 participated in this reductive formation of thiosulfate. This reaction was coupled to the bisulfite reductase-catalyzed reaction, which resulted in the reconstruction of a thiosulfate-forming pathway from bisulfite.